Niobium-doped diamond-like carbon coatings on metallic alloy and their tribological performance in biodiesel environment Environment - Maleque, Md. Abdul; Zawawi, Muhammad Zaidul Abrar; Efeoglu, Ihsan; Gulten, Gokhan; Rahman, Md Mustafizur; Zulkifli, Nurin Wahidah (Springer, 2025)
The tribo-component materials in automotive injector nozzle systems face challenges related to durability and longevity, leading to increased maintenance costs and negative environmental impacts. Diamond-like carbon (DLC) coatings can provide a promising solution to these issues. Therefore, this work aims to investi gate the coating characteristics of niobium-doped diamond-like carbon (Nb-DLC) on H13 tool steel and evaluate the tribological performance in biodiesel environment. Design Expert software was utilized to optimize the coating process parameters. Employing the Taguchi design of experiments, four samples (r1, r2, r3, and r4) were prepared with coating parameters of 3A target current, 2 µs duty time, and 50 V bias voltage. The primary methodologies involved characterizing the Nb-DLC coat ings on H13 tool steel synthesized using the Closed Field Unbalanced Magnetron Sputtering (CFUBMS) technique. Tribological tests were conducted using a High Frequency Reciprocating Rig (HFRR) wear tester according to ASTM D6079 stan dards under biodiesel conditions to evaluate wear and friction performance. The Nb-DLC coating thickness ranged from 3.2 to 7.0 µm in this investigation. Exper imental results demonstrated that the higher hardness and lowest wear rate were achieved in sample r4. This study reveals that the novel Nb-DLC coating signifi cantly enhances surface properties and improves tribological performance, making it a potential sustainable material for automotive engine injector nozzle components in biodiesel environment.